Location of the Internal Mammary Vessels for Microvascular Autologous Breast Reconstruction: The "1–2–3 Rule". Issue 1 (July 2018) - Lee, Christina Dami; Butterworth, James; Stephens, Robert E.; Wright, Barth; Surek, Christopher
Abstract : Background: Postmastectomy breast reconstruction provides psychosocial benefits in self-esteem, sexuality, and quality of life. Autologous procedures yield the highest overall patient satisfaction compared with implant-based breast reconstruction as the gold standard. The internal mammary vessels are the preferred recipient vessels for free flap breast reconstruction. The purpose of this study is to provide surgeons with a reliable method for locating the vessels intraoperatively. Methods: The internal mammary vessels were dissected bilaterally on 30 cadaveric specimens. Distances from the lateral sternal borders and the costochondral junctions to the internal mammary vessels at the second, third, and fourth costal levels were recorded. Descriptive bifurcation patterns were recorded. Initial dissection practicums were performed using the proposed safer dissection zone according to quantitative data. Results: Sixty internal mammary arteries and 120 internal mammary veins were studied at three costal levels, resulting in 180 sets of measurements. Distances from the lateral sternal border to the medial internal mammary vein were 6.12, 9.04, and 10.45 mm at costal levels 2, 3, and 4, respectively. Mean distances between costochondral junctions and internal mammary arteries were 12.80, 24.78, and 33.28 mm at costal levels 2, 3, and 4, respectively. Most internal mammary vein bifurcated at the third costal level, and the left side bifurcated higher than the right. Dissection practicums revealed that the proposed dissection zone was consistently reliable in locating the vessels. Conclusions: This study provides mean measurements from common bony landmarks to the internal mammary vessels, equipping surgeons with a reliable zone of dissection for recipient vessel exposure. This may decrease morbidity and improve outcomes in autologous breast reconstructions. Abstract : Supplemental Digital Content is available in the text.